Pelatihan Penanganan Pasca Cabut Gigi dengan Hyaluronic Acid bagi Dokter Gigi di Sidoarjo: Post-Tooth Extraction Management Training with Hyaluronic Acid for Dentists in Sidoarjo - Indrawati, Dwi Wahyu; Manurung, Rizky Briliant Syah; Endarti, Esa Wahyu; Mukti, Ria Andriani; Manurung, Muhammad Rizky Akbar (Proceedings of The ICECRS, 2025)
Post-extraction emergencies such as dry socket, uncontrolled bleeding, and infection remain significant challenges in dental practice. Hyaluronic acid (HA), a natural substance with anti-inflammatory and antibacterial properties, has been proven to accelerate wound healing and reduce post-extraction complications. This community service activity involved a training workshop on the clinical application of hyaluronic acid (HA) for dentists in Sidoarjo Regency, aimed at enhancing their knowledge and skills in hyaluronic acid (HA) use. The one-day training employed lectures, case discussions, and clinical simulations and was attended by 25 dentists. Results showed a 35% improvement in participants’ understanding of hyaluronic acid (HA)’s role in accelerating healing and preventing complications. Evaluation indicated that hyaluronic acid (HA) effectively reduces pain, prevents complications such as dry socket, and promotes wound reepithelialization. This training is expected to improve the standard of dental care and serve as a replicable model for other regions. The implementation of hyaluronic acid (HA) as a post-extraction protocol supports evidence-based practice and natural material innovation, leading to optimal clinical outcomes.